A Solution of the Generation Puzzle from Yang-Mills Duality - Chan, H; Tsou, S (2000)
A solution to the generation puzzle based on a nonabelian generalization of electric-magnetic duality is briefly reviewed. It predicts 3 and only 3 generations of fermions and explains the hierarchical mass spectrum as well as the main features in both the quark and lepton mixing matrices. A calculation to leading perturbative order already gives reasonable values to about half of the Standard Model parameters.